Normalization strategies for real-time expression data in Chlamydia trachomatis - Borges, V. (2012)
Since Chlamydia trachomatis is a genetically non-tractable pathogen, transcriptomics assumes a fundamental role for the better understanding of its biology. However, the suitability of endogenous controls for normalization of transcriptomic data in this bacterium still needs validation. We aimed to assess the stability of 10 genes for their potential use as endogenous controls in qPCR at both normal and stress (antibiotic treatment) growth conditions throughout the developmental cycle of three strains with different cell-appetence. Normalization was performed using the quantified bacterial genomes. We also tested the applicability of two widely used softwares (geNorm and Normfinder) to our data. For all strains, we found that 16SrRNA was the most stably expressed gene throughout the normal developmental cycle, but it was highly unstable under antibiotic exposure, suggesting prudence when using ribosomal genes as endogenous controls in expression experiments involving stress environments. The geNorm and Normfinder algorithms revealed contrasting results and seem inappropriate for the selected pool of genes. Considering the multiplicity of experimental conditions, there should be an in loco validation of endogenous controls, where 16SrRNA appears to be in the front line. Alternatively, normalization of expression data against genomic DNA, which is less influenced by experimental constraints (especially relevant for intracellular organisms) and stress conditions, likely constitutes a good option. The present study constitutes the first evaluation of putative endogenous controls for real-time expression assays in C. trachomatis